How to foster Sustainable Continuous Improvement: A cause-effect relations map of Lean soft practices - Federica Costa; Leonardo Lispi; Alberto Portioli Staudacher; Matteo Rossini; Kaustav Kundu; Fabiana Dafne Cifone (Operations Research Perspectives, 2019)
Lean Management (LM) represents a complex socio-technical system where both technical and social practices should be consistently implemented and integrated in order to foster a Continuous Improvement (CI) culture. Despite initial gains in operational performances due to the implementation of the most common and well-established Lean techniques, the great majority of the companies approaching Lean Manufacturing fail in achieving sustainable outcomes in the long term, and most of them eventually come back to their traditional way of doing business. Recognized the pivotal role of soft practices, the purpose of this study is to investigate the role played by the human factor in fostering the establishment of a Sustainable Continuous Improvement (SCI) environment. Starting from surveying the literature, a comprehensive framework including all the relevant soft practices related to LM has been developed. Then, authors proposed, for the first time, Decision-Making Trail and Evaluation Laboratory (DEMATEL) analysis applied to soft practices of SCI, that provides an innovative understanding of the relevant soft practices which foster SCI by showing cause-effect association among them. The proposed methodology reveals precious insights for scholars and practitioners who intend to approach and apply SCI. The impact relations map shows that some soft practices are initiators and some others enablers of the SCI and allows to identify the most relevant Critical Success Factors (CSF) and interrelationships amongst them. Results show that the key for a SCI is represented by a full engagement of the workforce, which must be triggered and supported by Top Management with the use of some leverages such as an effective communication, training and use of Kaizen events.
Keywords: 330; Lean manufacturing; Continuous improvement; Lean sustainability; Soft practices; Critical success factors; DEMATEL